Jan Patočka and the Global South: Latin American dissidence and Czech phenomenology - E. Brinton, Aspen (Pensando - Revista de Filosofia, 2023)
This paper argues that the phenomenological philosophy of Jan Patočka is relevant for understanding cases of political dissidence across the Global South. In particular, it examines three phenomena related to Latin American dissidence in order to show this relevance: the movement against femicide in ‘Ni Una Menos,’ the frequent murder of environmental activists defending the Amazon rainforest, and the historical experience of activist and psychoanalyst Felix Guattari chronicled in Molecular Revolution in Brazil (1982). These three phenomena are analyzed using Patocka’s oeuvre, including his concept of ‘solidarity of the shaken,’ his framework of the ‘three movements of existence,’ and in light of his critique of technology and mathematization as it relates to ‘living in truth.’ Overall, it argues that when Patočka’s ideas are deterritorialized in conversation with these phenomena of the Global South, the relevance of his ideas for understanding the existential aspects of historicity and political engagement hold up across time and place, affirming his legacy as a philosopher who can inspire both contemplation and action.